2011
DOI: 10.1590/s0102-71822011000200024
|View full text |Cite
|
Sign up to set email alerts
|

Satisfacción con la alimentación y la vida, un estudio exploratorio en estudiantes de la universidad de la frontera, Temuco-Chile

Abstract: Con el objetivo de explorar la relación entre la alimentación, como dominio de la vida, y el bienestar subjetivo en estudiantes universitarios, se aplicó una encuesta a una muestra no probabilística de 112 estudiantes universitarios. El cuestionario incluyó las escalas SWLS (Satisfaction with Life Scale), SWFL (Satisfaction with Food-related Life) y la frecuencia de consumo de distintos alimentos. Ambas escalas presentaron adecuados niveles de consistencia interna y la existencia de un solo factor para el tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 21 publications
(15 reference statements)
0
6
0
2
Order By: Relevance
“…: "Food and meals are positive elements"). The Spanish version of the SWFoL was used (Schnettler et al, 2011), which has shown good internal consistency in previous studies with adults in Chile Schnettler et al, 2018abc). Respondents were asked to indicate their degree of agreement with each statement using a 6-point Likert scale (1: completely disagree; 6: completely agree).…”
Section: Methodsmentioning
confidence: 99%
“…: "Food and meals are positive elements"). The Spanish version of the SWFoL was used (Schnettler et al, 2011), which has shown good internal consistency in previous studies with adults in Chile Schnettler et al, 2018abc). Respondents were asked to indicate their degree of agreement with each statement using a 6-point Likert scale (1: completely disagree; 6: completely agree).…”
Section: Methodsmentioning
confidence: 99%
“…H2: The proposed five factors structure which compose the scale will have well-adjusted with the data. , Regarding the second objective, previous studies have reported that university students assess their lives positively (Barraza & Ortiz, 2012;Domínguez-Espinoza, Salas, Contreras, & Procidano, 2011;Gómez, Villegas, Barrera, & Cruz, 2007;Martínez, 2004;Schnettler et al, 2011;Moyano, Cornejo, Carreño, & Muñoz, 2013;Schnettler et al, 2013;Zubieta & Delfino, 2010;Zubieta et al, 2012), which provides the descriptives hypothesis: (H 3 ) A level above the central point of the scale of life satisfaction by domains will be observed in university students. In relation to the third and fourth objectives, the current stateof-the-art reveals differences according to gender and socioeconomic level where women (Zubieta & Delfino, 2010;Zubieta et al, 2012) and the highest socioeconomic levels (Martínez, 2004;Zubieta & Delfino, 2010) present more positive assessments than their comparison groups, and it is therefore expected that: (H 4 ) In female university students, the level of life satisfaction by domains will be greater than in male university students.…”
Section: Introductionmentioning
confidence: 93%
“…According to previous studies with university students, the level of life satisfaction could affect a variety of life domains, such as eating behavior patterns (Schnettler, Miranda, Sepúlveda, & Denegri, 2011), physical and social well-being (Zubieta & Delfino, 2010), self-concept (Zegers, Rojas-Barahona, & Forster, 2009), future time perspective (Martínez, 2004), among other variables. Differences according to gender and socioeconomic level have also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a los conocimientos de los universitarios sobre alimentación saludable, la literatura señala que para mejorar la mala calidad de su dieta se requieren intervenciones para mejorar la información sobre el aporte nutricional de las comidas 24 y mejorar sus hábitos alimentarios 25 , los cuales pueden afectar favorablemente el desempeño académi-co de los estudiantes si se implementa desde el inicio de su carrera 26 , con acompañamiento al estudiante para que se produzca la modificación de los hábitos alimentarios 18 , asociados con motivos nutricionales o de salud y también con el disfrute 8 .…”
Section: Discussionunclassified
“…Respecto a los hábitos alimentarios, la literatura señala que en estudiantes universitarios no predomina un patrón racional de análisis nutricional, sino un patrón relacionado con aspectos sociales a los cuales se asocia el consumo de estos alimentos 8 .…”
Section: Introductionunclassified